Monastic Stories: Hagiography and History in the Panegyrics on Abraham of Farshut - Goehring, James E. (Cistercian studies quarterly, 2013)
The article focuses on history and hagiography in the panegyrics on Abraham of Farshut, who was a saint of the Coptic Church. It further explores the relationship between hagiography and history in terms of religious literature and Egyptian monasticism. It further states that many scholars working with hagiographical sources find their historical relevance on the basis of author's ideology.